Late Follicular Hyperprolactinemia (LF-HPRL) is not a disease - Allow, Ahmed Kaid Naji; Sadek S. M., Abdulmogny; Bracamonte, Maryam; Belqees, Ahmed Kaid (2014)
Prolactin (PRL) is an exceptional hormone of pituitary gland with important implications for normal reproduction as well as for sexual behavior. It increases in the first trimester of pregnancy (physiological hyperprolactinemia). The objective of this study is to evaluate the effectiveness of LF-HPRL as an indicator for early ongoing pregnancy in patients undergoing infertility treatment. Materials and patients: One hundred and eleven infertile women were involved in the present study. They were divided into: group A=76 pregnant women without anti-LF-HPRL therapy and 35 pregnant women with anti- LF-HPRL therapy as a group B. All women in both groups had been treated due to hyperprolactinemia until their PRL levels were normal. Later, after one cycle, both groups had been enrolled in a controlled ovarian hyperstimulation (COS). Their husbands were reproductively fertile. All women with an additional factor of infertility had been excluded. The COS was aimed to get 2-3 mature follicles/women/cycle. During study, the ovulation, pregnancy, abortion, cancelation and live-birth rates were evaluated. Results: no significant differences between the groups regarding age, BMI and baseline hormonal investigation (FSH, LH, LH/FSH, testosterone, estradiol and PRL (P<0.03). The progesterone level at the day 21 of cycle was significantly difference between study and control groups, (4.52±4.91 and 5.36±4.73, respectively, P<0.02). The serum PRL at the 28 day of ovulation induction cycle was significantly difference between study and control group (28.32±11.89 and 7.53±5.69, respectively, P<0.001). The ovulation, ongoing pregnancy, life-birth rates were significantly higher in study group in compare to control group (P<0.001). The early abortion and cancelation rates were significantly higher in control in compare to study groups (P<0.001). Conclusion: high level of serum prolactin levels in the late follicular menstrual phase or LF-HPRL in infertile women treated by ovulation induction after complete hyperplactinemic therapy could be used as an indicator for early pregnancy. Treatment of LF-HPRL not recommended.